Kontribusi Generasi Z Terhadap Tantangan Pada Sektor Pertanian Indonesia: Generation Z's Contribution to Challenges in Indonesia's Agricultural Sector - Satria, Muhammad Rangga; Rozaki, Zuhud; Wulandari, Retno; Nurlita, Mita (Universitas Muhammadiyah Yogyakarta, 2024)
the agricultural sector, and also increase productivity and participate in developing agricultural technology. There are problems that cause the process of progress in the agricultural sector to be hampered because according to the young generation, agricultural deposits are not in accordance with their interests and also do not want to grow crops, which on average tend to be interested in the office, service, economic and business sectors. In addition, young people in rural areas think that being a farmer has no future. The higher the level of education in rural areas, the lower the interest of youth to work in the agricultural sector. However, there are also a number of z-generations who are interested in working in the agricultural sector, which has the aim of advancing the agricultural sector, including through the use of technology and the development of agricultural production.